Cathode catalyst layer slurry, preparation method thereof and membrane electrode
By adding mesoporous carbon and other materials to the cathode catalytic layer slurry, a catalytic layer with high specific surface area and high porosity is formed, which solves the problem of difficulty in discharge of liquid water, and improves the oxygen delivery efficiency and the output power density of the fuel cell.
Patent Information
- Application Number
- CN202311266456.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the liquid water generated by the cathode catalytic layer cannot be discharged in time, blocking the pore structure, resulting in the inability to be transported to the catalyst surface in time, or the transportation efficiency is reduced, resulting in the reduction of the membrane electrode power generation efficiency.
A cathode catalytic layer slurry, including Pt-containing catalyst, mesoporous carbon, ionomer, water and low molecular alcohol, is used to form a catalytic layer with high specific surface area and high porosity through uniform mixing and dispersion treatment, ensuring the timely discharge of water and effective oxygen delivery.
It improves the oxygen transmission efficiency of the cathode catalytic layer, enhances the output power density of the fuel cell, and simplifies the preparation process, which is suitable for large-scale industrial production.
Smart Images

Figure CN119725581A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton exchange membrane fuel cells, and in particular to a cathode catalyst layer slurry and a preparation method thereof, and a membrane electrode. Background Art
[0002] Membrane electrode is the core component of proton exchange membrane fuel cell, which consists of proton exchange membrane, catalyst layer and gas diffusion layer.
[0003] The catalytic layer is an important component of the membrane electrode. The anode uses a catalyst to promote the oxidation reaction of hydrogen, which involves multiple processes such as oxidation reaction, gas diffusion, electron movement, proton movement, water migration, etc. The cathode uses a catalyst to promote the reduction reaction of oxygen, which involves oxygen reduction, oxygen diffusion, electron movement, proton movement, and the discharge of water generated by the reaction.
[0004] The water and oxygen at the cathode move through the pores generated by the catalyst layer and then transported to the catalyst surface. The generated water is discharged to the gas diffusion layer through these pores and then discharged from the fuel cell. Therefore, the ability to transport oxygen and water greatly limits the power generated by the fuel cell; sometimes the generated liquid water cannot be discharged from the catalyst layer in time, blocking the pore structure, resulting in the inability to transport oxygen to the catalyst surface in time, or the transport efficiency is reduced, which reduces the power generation efficiency of the membrane electrode.
[0005] Some existing technologies help the cathode catalyst layer to drain water by matching a more hydrophobic gas diffusion layer, thereby providing a channel for oxygen transport. However, the porosity of the prepared catalyst layer is limited, and the oxygen transport channel is limited. Another method is to control the porosity of the catalyst layer by adjusting the cathode ink solvent ratio, but this method is not effective in actual application and cannot effectively improve the membrane electrode power generation efficiency.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] One of the purposes of the present invention is to provide a cathode catalyst layer slurry to alleviate the technical problem in the prior art that liquid water generated by the cathode catalyst layer cannot be discharged from the catalyst layer in time, blocking the pore structure, resulting in oxygen being unable to be transported to the catalyst surface in time, or the transport efficiency is reduced, thereby reducing the power generation efficiency of the membrane electrode.
[0008] A second object of the present invention is to provide a method for preparing cathode catalyst layer slurry.
[0009] A second object of the present invention is to provide a membrane electrode.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The first aspect of the present invention provides a cathode catalyst layer slurry, comprising, by weight, 1-20 parts of a Pt-containing catalyst, 0.1-3 parts of mesoporous carbon, 1-20 parts of an ionomer, 10-60 parts of water, and 10-60 parts of a low molecular alcohol.
[0012] Furthermore, the specific surface area of the mesoporous carbon is 400 m 2 / g-1000m 2 / g, preferably 500m 2 / g-800m 2 / g.
[0013] Furthermore, the platinum content in the Pt-containing catalyst is 20wt.%-60wt.%;
[0014] Preferably, the Pt-containing catalyst comprises Pt / C or Pt-alloy / C.
[0015] Furthermore, the ionomer includes at least one of perfluorosulfonic acid resin, sulfonated trifluorostyrene resin, and polymethylphenylsulfonic acid siloxane resin, preferably perfluorosulfonic acid resin.
[0016] Furthermore, the low molecular alcohol includes at least one of methanol, ethanol, ethylene glycol, n-propanol, isopropanol and glycerol.
[0017] The second aspect of the present invention provides a method for preparing the cathode catalyst layer slurry, comprising uniformly mixing the Pt-containing catalyst, the mesoporous carbon, water and a low molecular alcohol, and finally adding the ionomer and dispersing them uniformly to obtain the cathode catalyst layer slurry.
[0018] Furthermore, the dispersion method includes ultrasonic dispersion, ultra-high speed shear dispersion, nano-homogenizer dispersion, mechanical stirring dispersion or ball milling dispersion.
[0019] Furthermore, the dispersion speed is 1500rpm-5000rpm, and the time is 20min-40min.
[0020] Preferably, a degassing treatment is also included after the dispersion.
[0021] Preferably, the rotation speed of the degassing treatment is 500 rpm-1000 rpm, and the time is 3 min-8 min.
[0022] A third aspect of the present invention provides a membrane electrode, comprising an anode gas diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode gas diffusion layer;
[0023] The cathode catalyst layer is formed by coating the cathode catalyst layer slurry described in the first aspect.
[0024] Further, the coating is performed by slit coating, doctor blade coating, ultrasonic spray coating or screen printing.
[0025] Compared with the prior art, the present invention has at least the following beneficial effects:
[0026] The cathode catalyst layer slurry provided by the present invention has mesoporous carbon added to the slurry. The mesoporous carbon has a high specific surface area and a high porosity, and the pore structure is orderly and interconnected, which is conducive to the timely discharge of water generated on the catalyst layer, provides more oxygen transport channels, improves the oxygen transmission efficiency of the cathode catalyst layer, and improves the output power density of the fuel cell.
[0027] The preparation method provided by the present invention firstly mixes the Pt-containing catalyst and the mesoporous carbon uniformly with water and low molecular alcohol, then adds the ionomer to disperse, distributes and mixes, improves the dispersion efficiency, makes the prepared slurry more uniform, and is conducive to obtaining an isotropic cathode catalyst layer. The preparation method has a simple process, a high degree of mechanization, and is suitable for large-scale industrial production.
[0028] The membrane electrode provided by the present invention uses a cathode catalyst layer with better performance, thereby improving the utilization rate of the catalyst and further improving the performance of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 A schematic diagram of the effect of mesoporous carbon in the cathode catalyst layer provided by the present invention. DETAILED DESCRIPTION
[0031] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] The first aspect of the present invention provides a cathode catalyst layer slurry, comprising, by weight, 1-20 parts of a Pt-containing catalyst, 0.1-3 parts of mesoporous carbon, 1-20 parts of an ionomer, 10-60 parts of water, and 10-60 parts of a low molecular alcohol.
[0033] The cathode catalyst layer slurry provided by the present invention has mesoporous carbon added to the slurry. The mesoporous carbon has a high specific surface area and a high porosity, and the pore structure is orderly and connected. The effect diagram is shown in FIG. Figure 1 As shown, the pore structure provided in the mesoporous carbon is conducive to the timely discharge of water generated on the catalyst layer, providing more oxygen transport channels, improving the oxygen transmission efficiency of the cathode catalyst layer, and improving the output power density of the fuel cell.
[0034] Mesoporous carbon is a new type of non-silicon-based mesoporous material with a pore size of 2nm<50nm and a huge specific surface area (up to 2500m 2 / g) and pore volume (up to 2.25 cm 3 / g), the pore size can be adjusted within a certain range; the mesopores have various shapes, and the pore wall composition, structure and properties are adjustable. Most importantly, they have an ordered mesopore channel structure and are connected, which is conducive to providing channels for water output and oxygen delivery.
[0035] When the amount of mesoporous carbon is less than 0.1 parts, the mesoporous structure is insufficient and the improvement on the technical effect is not significant; when the amount of mesoporous carbon is greater than 3 parts, it accounts for too large a proportion in the slurry, which will reduce the amount of Pt-containing catalyst, thereby resulting in poor catalytic effect and reducing the output power of the manufactured fuel cell.
[0036] Among them, the weight portion of Pt catalyst is typically but not limited to 1 part, 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts, 19 parts or 20 parts; the weight portion of mesoporous carbon is typically but not limited to 0.1 parts, 0.5 parts, 1 parts, 2 parts or 3 parts; the weight portion of ionomer is typically but not limited to 1 part, 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts, 19 parts or 20 parts; the weight portion of water is typically but not limited to 10 parts, 20 parts, 30 parts, 40 parts, 50 parts or 60 parts; the weight portion of low molecular weight alcohol is typically but not limited to 10 parts, 20 parts, 30 parts, 40 parts, 50 parts or 60 parts.
[0037] It should be noted that, during use, the ionomer is generally used in the form of a dispersion, in which the mass fraction of the ionomer is 2wt.%-40wt.%. The amount of ionomer in the cathode catalyst layer slurry has been converted into the actual content.
[0038] Furthermore, the specific surface area of the mesoporous carbon is 400 m 2 / g-1000m 2 / g, preferably 500m 2 / g-800m 2 / g.
[0039] In some embodiments of the present invention, the specific surface area of the mesoporous carbon is typically, but not limited to, 400 m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g or 1000m 2 / g.
[0040] Furthermore, the platinum content in the Pt-containing catalyst is 20wt.%-60wt.%.
[0041] Typically, but not limiting, the platinum content of the Pt-containing catalyst may be 20 wt.%, 30 wt.%, 40 wt.%, 50 wt.% or 60 wt.%.
[0042] Preferably, the Pt-containing catalyst comprises Pt / C or Pt-alloy / C.
[0043] Pt-alloy refers to an alloy composed of Pt and other metal elements. The present invention does not specifically limit other metal elements, and any metal element commonly used in the art that can form an alloy with Pt and can serve as a cathode catalyst can be used.
[0044] Furthermore, the ionomer includes at least one of perfluorosulfonic acid resin, sulfonated trifluorostyrene resin, and polymethylphenylsulfonic acid siloxane resin, preferably perfluorosulfonic acid resin.
[0045] Furthermore, the low molecular alcohol includes at least one of methanol, ethanol, ethylene glycol, n-propanol, isopropanol and glycerol.
[0046] The second aspect of the present invention provides a method for preparing the cathode catalyst layer slurry, comprising uniformly mixing the Pt-containing catalyst, the mesoporous carbon, water and a low molecular alcohol, and finally adding the ionomer and dispersing them uniformly to obtain the cathode catalyst layer slurry.
[0047] The preparation method provided by the present invention firstly mixes the Pt-containing catalyst and the mesoporous carbon uniformly with water and low molecular alcohol, then adds the ionomer to disperse, distributes and mixes, improves the dispersion efficiency, makes the prepared slurry more uniform, and is conducive to obtaining an isotropic cathode catalyst layer. The preparation method has a simple process, a high degree of mechanization, and is suitable for large-scale industrial production.
[0048] Furthermore, the dispersion method includes ultrasonic dispersion, ultra-high speed shear dispersion, nano-homogenizer dispersion, mechanical stirring dispersion or ball milling dispersion.
[0049] Furthermore, the dispersion speed is 1500rpm-5000rpm, and the time is 20min-40min.
[0050] Typically but not limiting, the dispersion speed may be 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm or 5000 rpm; the dispersion time may be 20 min, 25 min, 30 min, 35 min or 40 min.
[0051] Preferably, a degassing treatment is also included after the dispersion.
[0052] The purpose of degassing is to ensure the quality of the cathode catalyst layer slurry and to prevent bubbles from causing surface defects of the cathode catalyst layer or weakening the performance of the cathode catalyst layer during the curing or drying process.
[0053] Preferably, the rotation speed of the degassing treatment is 500 rpm-1000 rpm, and the time is 3 min-8 min.
[0054] Typically but not limiting, the rotation speed of the degassing treatment may be 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm; and the time may be 3 min, 4 min, 5 min, 6 min, 7 min or 8 min.
[0055] A third aspect of the present invention provides a membrane electrode, comprising an anode gas diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode gas diffusion layer;
[0056] The cathode catalyst layer is formed by coating the cathode catalyst layer slurry described in the first aspect.
[0057] The membrane electrode provided by the present invention uses a cathode catalyst layer with better performance, thereby improving the utilization rate of the catalyst and further improving the performance of the membrane electrode.
[0058] Further, the coating is performed by slit coating, doctor blade coating, ultrasonic spray coating or screen printing.
[0059] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0060] Example 1
[0061] This embodiment provides a cathode catalyst layer slurry, and the preparation process is as follows:
[0062] In a container, 3.4 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E) particles were moistened with 14 g of water, and then 0.05 g of mesoporous carbon (Xianfeng Nano-XFP05, specific surface area 600 m 2 / g) powder, add 16.8g of n-propanol and stir for 2min, continue to add 5.5g of -ionomer solution (DuPont-D2020), stir for 5min; the mixed slurry is ball-milled at a speed of 2500rpm for 30min, and finally the slurry is degassed at a speed of 700rpm for 5min to obtain the cathode catalyst layer slurry.
[0063] Example 2
[0064] This embodiment provides a cathode catalyst layer slurry. The difference from Embodiment 1 is that the amount of mesoporous carbon added is 0.17 g. The remaining raw materials and methods are the same as those in Embodiment 1 and are not described again.
[0065] Example 3
[0066] This embodiment provides a cathode catalyst layer slurry. The difference from Embodiment 1 is that the amount of mesoporous carbon added is 0.34 g, and the other raw materials and methods are the same as those in Embodiment 1 and are not described again.
[0067] Example 4
[0068] This embodiment provides a cathode catalyst layer slurry. The difference from Embodiment 1 is that the amount of mesoporous carbon added is 0.51 g, and the other raw materials and methods are the same as those in Embodiment 1 and are not described again.
[0069] Example 5
[0070] This embodiment provides a cathode catalyst layer slurry. The difference from Embodiment 1 is that the amount of mesoporous carbon added is 0.68 g, and the remaining raw materials and methods are the same as those in Embodiment 1 and are not described again.
[0071] Example 6
[0072] This embodiment provides a cathode catalyst layer slurry. The difference from Embodiment 1 is that the amount of mesoporous carbon added is 0.85 g, and the other raw materials and methods are the same as those in Embodiment 1 and are not described again.
[0073] Example 7
[0074] This embodiment provides a cathode catalyst layer slurry, and the preparation process is as follows:
[0075] In a container, 8 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E) particles were moistened with 35 g of water, and 2.3 g of mesoporous carbon (specific surface area 600 m 2 / g) powder, add 32g of n-propanol and stir for 5min, continue to add 12g of ionomer solution (DuPont-D2020), and stir for 8min; the mixed slurry is ball-milled at a speed of 2500rpm for 35min, and finally the slurry is degassed at a speed of 700rpm for 5min to obtain the cathode catalyst layer slurry.
[0076] Example 8
[0077] This embodiment provides a cathode catalyst layer slurry, and the preparation process is as follows:
[0078] In a container, 20 g of Pt / C catalyst (Tanaka Precious Metals Co., Ltd. - TEC10E50E) particles were moistened with 60 g of water, and then 5 g of mesoporous carbon (Xianfeng Nano-XFP05, specific surface area 600 m 2 / g) powder, add 55g of n-propanol and stir for 5min, continue to add 25g of ionomer solution (DuPont-D2020), and stir for 8min; the mixed slurry is ball-milled at a speed of 2500rpm for 40min, and finally the slurry is degassed at a speed of 700rpm for 5min to obtain the cathode catalyst layer slurry.
[0079] Comparative Example 1
[0080] This comparative example provides a cathode catalyst layer slurry. The difference from Example 1 is that no mesoporous carbon is added. The remaining raw materials and methods are the same as those in Example 1 and will not be described again.
[0081] Comparative Example 2
[0082] This comparative example provides a cathode catalyst layer slurry. The difference from Example 1 is that activated carbon is used instead of mesoporous carbon. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.
[0083] Examples 9-16
[0084] These embodiments provide some membrane electrodes, corresponding to the cathode catalyst layer slurry provided in embodiments 1-8, which is sprayed on a polytetrafluoroethylene film by ultrasonic spraying, and the Pt loading is 0.3 mg / cm 2 Place it in an oven and dry it at 70 degrees for 5 minutes to prepare the cathode. The sample area is 25cm 2 .
[0085] The anode coating uses an internal standard sample with a Pt loading of 0.05 mg / cm2 , the cathode and cathode coatings were transferred to the proton exchange membrane (Gore-12 micron) at 140°C and 14 kgf / cm 2 , the anode and cathode gas diffusion layers use Toray XGL-R-055 to obtain a membrane electrode.
[0086] Comparative Examples 3-4
[0087] These comparative examples provide some membrane electrodes, corresponding to the cathode catalyst layer slurry provided in comparative examples 1-2, which is sprayed on a polytetrafluoroethylene film by ultrasonic spraying, and the Pt loading is 0.3 mg / cm 2 Place it in an oven and dry it at 70 degrees for 5 minutes to prepare the cathode. The sample area is 25cm 2 .
[0088] The anode coating uses an internal standard sample with a Pt loading of 0.05 mg / cm 2 , the cathode and cathode coatings were transferred to the proton exchange membrane (Gore-12 micron) at 140°C and 14 kgf / cm 2 , the anode and cathode gas diffusion layers use Toray XGL-R-055 to obtain a membrane electrode.
[0089] Test Example 1
[0090] The cathodes obtained in Examples 9-16 and Comparative Examples 3-4 were tested for porosity using the BET method. The obtained data are shown in Table 1.
[0091] Table 1
[0092] Porosity / % Example 9 57 Example 10 60 Embodiment 11 66 Example 12 74 Example 13 71 Embodiment 14 62 Embodiment 15 61 Example 16 59 Comparative Example 3 54 Comparative Example 4 51
[0093] Test Example 2
[0094] The membrane electrodes obtained in Examples 9-16 and Comparative Examples 3-4 were tested with a test area of 25 cm 2 The test conditions are temperature 70℃, anode and cathode humidity 40% / 40%, cathode and cathode metering ratio 1.5 / 2, cathode and cathode back pressure 150KPa / 150KPa. The current density is recorded as 1.0A / cm 2 and 2.0A / cm 2 The voltage values under the conditions are shown in Table 2 below.
[0095] Table 2
[0096] <![CDATA[Voltage / V @ 1.0 A / cm 2 > <![CDATA[Voltage / V @ 2.0 A / cm 2 > Example 9 0.726 0.609 Example 10 0.729 0.617 Embodiment 11 0.736 0.630 Example 12 0.744 0.651 Example 13 0.739 0.644 Embodiment 14 0.731 0.623 Embodiment 15 0.730 0.618 Example 16 0.728 0.613 Comparative Example 3 0.723 0.604 Comparative Example 4 0.701 0.563
[0097] It can be seen from Table 1 and Table 2 that under the same current, the voltage of the membrane electrode is positively correlated with the cathode porosity. As the porosity increases, the voltage increases and the performance improves. Moreover, the cathode porosity varies with the mass of added mesoporous carbon, but is larger than the cathode of Comparative Example 3 without adding mesoporous carbon, and the best is Example 12.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cathode catalyst layer slurry, characterized in that: The invention comprises, by weight, 1 to 20 parts of a Pt-containing catalyst, 0.1 to 3 parts of mesoporous carbon, 1 to 20 parts of an ionomer, 10 to 60 parts of water and 10 to 60 parts of a low molecular alcohol.
2. The cathode catalyst layer slurry according to claim 1, characterized in that: The specific surface area of the mesoporous carbon is 400 m 2 / g-1000m 2 / g, preferably 500m 2 / g-800m 2 / g.
3. The cathode catalyst layer slurry according to claim 1, characterized in that: The platinum content of the Pt-containing catalyst is 20wt.%-60wt.%; Preferably, the Pt-containing catalyst comprises Pt / C or Pt-alloy / C.
4. The cathode catalyst layer slurry according to claim 1, characterized in that: The ionomer includes at least one of perfluorosulfonic acid resin, sulfonated trifluorostyrene resin, and polymethylphenylsulfonic acid siloxane resin, and is preferably perfluorosulfonic acid resin.
5. The cathode catalyst layer slurry according to claim 1, characterized in that: The low molecular alcohol includes at least one of methanol, ethanol, ethylene glycol, n-propanol, isopropanol and glycerol.
6. A method for preparing a cathode catalyst layer slurry according to any one of claims 1 to 5, characterized in that: The Pt-containing catalyst, the mesoporous carbon, water and low-molecular alcohol are mixed evenly, and finally the ionomer is added and dispersed evenly to obtain the cathode catalyst layer slurry.
7. The preparation method according to claim 6, characterized in that: The dispersion method includes ultrasonic dispersion, ultra-high speed shear dispersion, nano homogenizer dispersion, mechanical stirring dispersion or ball milling dispersion.
8. The preparation method according to claim 6, characterized in that: The dispersion speed is 1500rpm-5000rpm, and the time is 20min-40min; Preferably, it also includes a degassing process after dispersion; Preferably, the rotation speed of the degassing treatment is 500 rpm-1000 rpm, and the time is 3 min-8 min.
9. A membrane electrode, characterized in that: It includes an anode gas diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode gas diffusion layer; The cathode catalyst layer is formed by coating the cathode catalyst layer slurry according to any one of claims 1 to 5.
10. The membrane electrode according to claim 9, characterized in that: The coating is performed by slot coating, knife coating, ultrasonic spray coating or screen printing.